2018
DOI: 10.1177/2050312118790426
|View full text |Cite
|
Sign up to set email alerts
|

An Internet-based survey of the dance fitness program OULA

Abstract: Background:OULA is a high-energy dance workout to top 40 hits that is inspired by yoga and non-impact aerobics. Created in Missoula, Montana, the program has been gaining national and international popularity. To understand the demographic composition, reasons for attending OULA, and experiences with depression/anxiety, we conducted an Internet-based survey.Methods:A pilot descriptive cross-sectional Internet-based survey was created in Qualtrics and distributed through social media and flyers.Results:The 38-i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 58 publications
(63 reference statements)
0
3
0
Order By: Relevance
“…Although PALMS was not tailored for yogi motivation study, it perfectly incorporates the major reasons for yoga practice reported in successive studies, encompassing healthy body [55], more active lifestyle [56], physical fitness [33], better appearance [57], stronger control of emotion [58], personal mental growth [59], feeling like part of a community [60], and social engagement [34]. The only thing missing from PALMS seems to be spirituality related appeals [61], which may be explained by PALMS focusing on physical activities whereas spirituality is highly mental.…”
Section: Yogi Motivationmentioning
confidence: 99%
“…Although PALMS was not tailored for yogi motivation study, it perfectly incorporates the major reasons for yoga practice reported in successive studies, encompassing healthy body [55], more active lifestyle [56], physical fitness [33], better appearance [57], stronger control of emotion [58], personal mental growth [59], feeling like part of a community [60], and social engagement [34]. The only thing missing from PALMS seems to be spirituality related appeals [61], which may be explained by PALMS focusing on physical activities whereas spirituality is highly mental.…”
Section: Yogi Motivationmentioning
confidence: 99%
“…First, the attrition rate in this study was much higher than expected. Namely, in an Internet survey of OULA â , the authors report that the majority of the sample attended OULA â for 4-5 years (Hellem and Ferguson 2018). In the current study, n=30 (56.6% attrition rate) women dropped out of the study, mostly due to protocol non-compliance.…”
Section: Limitationsmentioning
confidence: 60%
“…A commonly used slogan in OULA â is, "it's not about how it looks, but about how it feels," encouraging participants to concentrate on how they feel while dancing and ignore how they look. In an Internet-based survey of OULA â participants, the authors report that the majority of OULA â participants are women and that the top two reasons for attending OULA â are for exercise and stress relief/improve mood (Hellem and Ferguson 2018).…”
Section: Introductionmentioning
confidence: 99%